1994
DOI: 10.1111/j.1365-2958.1994.tb01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Acinetobacter calcoaceticus recA and its contribution to intracellular gene conversion

Abstract: The Acinetobacter calcoaceticus pcaJ and catJ genes, nearly identical in DNA sequence, differ in transcriptional control and are separated by more than 20 kb of chromosomal DNA. The pcaJ3125 mutation is repaired frequently in organisms containing the wild-type catJ gene. This high-frequency repair is eliminated in strains lacking the catJ gene, which suggests that recombination between the homologous catJ and pcaJ genes contributes to the high-frequency repair of the pcaJ3125 mutation. We report here that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 28 publications
(16 reference statements)
2
33
0
Order By: Relevance
“…In agreement with this, it was recently observed that the upstream sequence of the A. calcoaceticzls recA gene is not preceded by a LexA-binding motif (Gregg-Jolly & Ornston, 1994). The promoter regions of the recA genes of T.ferrooxidans (Ramesar etal., 1989), N .…”
Section: Discussionsupporting
confidence: 56%
“…In agreement with this, it was recently observed that the upstream sequence of the A. calcoaceticzls recA gene is not preceded by a LexA-binding motif (Gregg-Jolly & Ornston, 1994). The promoter regions of the recA genes of T.ferrooxidans (Ramesar etal., 1989), N .…”
Section: Discussionsupporting
confidence: 56%
“…The lack of a LexA protein has also been previously reported in Bacillus fragilis (17), Thiobacillus ferrooxidans (35), Porphyromonas gingivalis (12), and Acinetobacter calcoaceticus (18). In radiation-resistant Deinococcus radiodurans LexA is present, but cleavage is not enhanced by recA expression (30 (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Conversion is less common in bacteria, where the DNA is mostly unique, but it occurs between the rrn operons, which are members of a multigene family (9,10). In addition, conversion of the Salmonella phase 1 flagellin gene fliC to the phase 2 gene fliB in E. coli has been demonstrated (24), and the catIJF and pcaIJF genes of Acinetobacter calcoaceticus, which have nearly identical nucleotide sequences, convert each other in a recA-dependent process at rates of about 10 Ϫ6 (8,16). The following points support the hypothesis that dispersion and sequence maintenance of IVSs is due to gene conversion.…”
Section: Discussionmentioning
confidence: 99%